Fitness Analysis Of Water Suitability For Seaeed Cultivation Kappahycus Alvarezii In South Buton Regency, Southeast Sulawesi - Fadhli Insani Ihsan; Hasni Y. Azis; Muhammad Anshar Amran (International Journal of Science, Technology & Management, 2021)
Seaweed cultivation in Indonesia is more focused on the production of Kappaphycus alvarezii species as a carrageenan producer. Land suitability analysis is an important stage in the preparation of spatial planning for coastal areas. This study aims to determine the appropriate location of the waters based on physical and chemical parameters using GIS. The research method is survey methods to get actual data related to seaweed cultivation activities. The spatial analysis of land suitability was carried out with a geographic information system based on the results of the x-weight score. The results of the analysis show that the spatial distribution that can be used for seaweed cultivation in the Batauga sub-district is 280 ha (very suitable) and Sampolawa 519 ha (very suitable), 838 ha (suitable), 234 ha (unsuitable).